The Influence of Brand Image and Service Quality on Indihome Customer Loyalty at PT Telekomunikasi Indonesia (Telkom) in Gunungsitoli City - Telaumbanua, Rinta Astuti; Mendrofa, Yupiter; Zalukhu, Yuterlin; Bate'e, Maria Magdalena (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
The rapid advancement of communication technology and the increasing demand for internet access have intensified competition among internet service providers in Indonesia. IndiHome, as a leading product of PT. Telekomunikasi Indonesia (Telkom), faces challenges in sustaining customer loyalty, particularly in regions such as Gunungsitoli City where infrastructure limitations often lead to unstable connections and delayed technical responses. This study aims to analyze the influence of brand image and service quality on customer loyalty toward IndiHome in Gunungsitoli. A quantitative approach was employed, with data collected through questionnaires distributed to 73 customers. The research variables included brand image and service quality as independent variables, and customer loyalty as the dependent variable. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The findings reveal that brand image has a positive and significant effect on customer loyalty. Similarly, service quality also exerts a positive and significant influence on customer loyalty. Simultaneously, both brand image and service quality significantly affect loyalty. The coefficient of determination (R²) of 0.529 indicates that 52.9% of customer loyalty is explained by these two variables, while the rest is influenced by other factors not examined in this study.